Electrophysiological classification of CACNA1G gene variants associated with neurodevelopmental and neurological disorders - Davakan, Amaël; Cmarko, Leos; Ribeiro Oliveira-Mendes, Barbara; Bernat, Claire; Boulali, Najlae; Montnach, Jérôme; Vallee, Stephanie E.; Dinulos, Mary B.; Burglen, Lydie; Cantagrel, Vincent; Weiss, Norbert; Nicole, Sophie; et al. (Frontiers in Pharmacology, 2025)
This study highlights the complementarity of automated patch-clamp (APC) and manual patch-clamp (MPC) approaches to describe the electrophysiological properties of eighteen Cav3.1 calcium channel variants associated with various neurological conditions. Current density was measured efficiently for all variants in APC experiments, with four variants (p.V184G, p.N1200S, p.S1263A and p.D2242N) showing elevated current densities, compared to wild-type Cav3.1 channel, while six variants (p.M197R, p.V392M, p.F956del, p.I962N, p.I1412T, and p.G1534D) displayed reduced current densities, and were therefore preferentially studied using MPC. The electrophysiological properties were well preserved in APC (e.g., inactivation and deactivation kinetics, steady-state properties), with only the APC-MPC correlation for activation kinetics being less robust. In addition, neuronal modeling, using a deep cerebellar neuron (DCN) environment, revealed that most of the variants localized to the intracellular gate (S5 and S6 segments) could increase DCN spike frequencies. This DCN firing was highly dependent on current density and further pointed to the gain-of-function (GOF) properties of p.A961T and p.M1531V, the two recurrent variants associated with Spinocerebellar Ataxia type-42 with Neurodevelopmental Deficit (SCA42ND). Action-potential (AP) clamp experiments performed using cerebellar and thalamic neuron activities further established the GOF properties of p.A961T and p.M1531V variants. Overall, this study demonstrates that APC is well-suited for high-throughput analysis of Cav3.1 channel variants, and that MPC complements APC for characterizing low-expression variants. Furthermore, in silico modeling and AP clamp experiments reveal that the gain- or loss-of-function properties of the variants are determined by how the Cav3.1 channel decodes the electrophysiological context of a neuron.